Effective education for learners with exceptionalities - Obiakor, Festus E.; Utley, Cheryl Anita Rose; Rotatori, Anthony F. (Advances in special education ;, 2003)
The use of the Internet to post information on teaching children with exceptionalities has led to problems for professionals who prefer such knowledge to be screened for accuracy. This volume includes useful, validated information that will help teachers to teach children with exceptionalities more effectively. The authors argue that effective education must facilitate the identification, evaluation, and placement and instructional programming for learners with exceptionalities. Based upon the school improvement and effective education literature and standards-based reform movement, schools must adopt principles of school effectiveness and offer classroom instruction that is based upon a clear assessment of the instructional needs of learners with exceptionalities and the implementation of interventions to maximize their potential and classroom performance. The book is designed to examine research from the disciplines of psychology, sociology, organizational theory, curriculum and instruction, and special education to address the critical issues related to the psychology of effective education for learners with exceptionalities. Contributors address a broad range of topics for restructuring general and special education into a unified system of education. Issues of labeling, classification, and identification; a continuum of educational and service delivery alternatives; curriculum and instruction; assessment and evaluation; distribution of funding resources; responsibilities; rationales for the grouping; and tracking of students are discussed across categories of exceptionalities. Part I of this book is organized around current perspectives and paradigms reflecting the authors' professional knowledge base in special education and the unification of general and special education into a comprehensive service delivery system. Part II specifically addresses a range of issues and topics of effective education for learners with exceptionalities. Part III addresses a range of issues and topics of effective education for learners with exceptionalities across the life span and for special student populations.